Penanaman Nilai-Nilai Karakter dalam Fenomena Sosiolinguistik di Sekolah Dasar - Badawi, Badawi (Institut Penelitian Matematika, Komputer, Keperawatan, Pendidikan dan Ekonomi (IPM2KPE), 2020)
This study aims to determine the inculcation of character values ​​by teachers in sociolinguistic phenomena in elementary schools. The method in this research is descriptive qualitative. The school that is the focus of the research is SD Ibnu Rusyd which is located in Kotabumi, North Lampung. The subjects in this study were 10 homeroom teachers. Collecting data in this study using observation, interviews and documentation. The results showed that the regional languages ​​of Ibnu Rusyd Islamic Elementary School students consisted of six regional languages ​​namely Javanese, Lampung, Sumendo, Palembang, Sundanese and Minang. There are 5 (five) foreign languages ​​used, namely English, Arabic, Chinese, Korean, and Indian. The inculcation of character values ​​by elementary school teacher Ibnu Rushd in the face of sociolinguistic phenomena, namely Islamic character values, tolerance, friendship, politeness, love of the country, national spirit, and curiosity. Keywords: Character, Value, Sociolinguistics.